Business Law - Nguyen, Bich Thao (Khoa Quốc tế, ĐHQGHN, 2020)
The course provides fundamental knowledge about the traders and commercial activities. Additionally, this course also gives students knowledge about commercial dispute resolutions, particularly commercial dispute resolutions outside the court. This course is designed with a plethora of learning activities designed to capture the students’ attention. In order for these learning activities to be successful, it is mandatory for the students to participate. This requires the students to be prepared, engage in the discussions and present information that pertains to the subject.